Analysis of the Effects of Different Orthodontic Appliances on Salivary pH Levels: An In vitro Approach - Mohammad K. Alam; Mohammad Y. Hajeer; Mashael Z. Alfuhigi; Mohammed A. Alrubaysh; Abdulmajeed F. Alsabilah; Moath A. Alslai (Wolters Kluwer Medknow Publications, 2024)
Background: Orthodontic appliances can influence the oral environment, including salivary pH levels, which play a crucial role in maintaining oral health. Understanding how different orthodontic appliances affect salivary pH levels can help in improving treatment outcomes and minimizing potential side effects. Materials and Methods: In this in vitro study, we evaluated the effects of various orthodontic appliances on salivary pH levels using a simulated oral environment. Four different types of orthodontic appliances were tested: traditional metal braces, ceramic braces, lingual braces, and clear aligners. Saliva samples were collected and subjected to pH measurements using a standardized method. The pH measurements were recorded at three different time intervals: immediately after appliance placement, after 24 hours, and after 48 hours. Results: The initial pH values varied among the different orthodontic appliances: metal braces (pH 7.2), ceramic braces (pH 7.4), lingual braces (pH 7.1), and clear aligners (pH 7.5). After 24 hours, there was a decrease in pH levels for all groups: metal braces (pH 6.8), ceramic braces (pH 7.0), lingual braces (pH 6.7), and clear aligners (pH 7.2). After 48 hours, the pH levels continued to decrease: metal braces (pH 6.5), ceramic braces (pH 6.8), lingual braces (pH 6.4), and clear aligners (pH 6.9). Conclusion: Our findings suggest that different orthodontic appliances have varying effects on salivary pH levels. Metal braces and lingual braces tend to cause a more pronounced decrease in salivary pH compared to ceramic braces and clear aligners. Monitoring salivary pH levels during orthodontic treatment may be beneficial in identifying potential risks to oral health and implementing appropriate interventions.